STUDI KELAYAKAN PENDIRIAN LEMBAGA PENYIARAN PUBLIK (LPP) LOKAL TELEVISI DI KABUPATEN BANYUMAS - Dwi Rudi Hartoyo (Widyariset, 2010)
This study has conducted to know readiness and feasibility of the Local Government of Banyumas that it willfound Broadcasting Institute of Public (LPP Local) of television as means of government to submit more information.Method which used in this study is survey technique, the results showed that there were 97.3% of Banyumaspopulations, they confessing like to watch on the TV, Public Television of men (89.2%) and woman (92.3%) replyingto require Public TV, while if asked approval of founding of public television (63%) respondents consists of men(58.8%) and from woman (67.3%) answered agree with reason to add knowledge and information about Banyumas.If It saw from views and community expectations on public television program based to results of broadcast programcomposition survey involving news bulletin (81.53%), drama/sinetron (48.45%), television debate and music ofdangdut ( 27.69%) and puppets (20.76%), while for the contents of event Appeal Television of Banyumas can raiseup local potency over 50%, regional (Central Java) 25% and national scale 25%.